Development of the insulation materials from coal fly ash, perlite, clay and linseed oil - Balo, Figen; Ucar, Aynur; Lütfi Yücel, Halit (My University, 2010)
The effect of coal fly ash (FA), clay (C), perlite (P) and epoxidized linseed oil (ELO) on the thermal and mechanical properties of insulation materials was investigated. The properties examined include density, thermal conductivity coefficient, compressive strength and tensile strength. A number of insulation material compositions were prepared with the FA, C, perlite and ELO. The results showed that compressive-tensile strength of the insulation material decreased when the high fly ash ratio and high epoxidized linseed oil ratio used in the preparation of the insulation material composition. The compressive and tensile strengths varied from 10.01 to 1.107 MPa and 8.38 to 1.013 MPa, respectively. The minimum thermal conductivity of 0.313 W/mK observed for the sample (L36) made with a 60% FA/30% C/10% P ratio and 50% ELO processed at 200°C. It is increased with the decrease of ELO and FA. Results indicate an interesting potential for the coal fly ash recycling and epoxidized linseed oil renewable to produce useful materials.
Keywords: Epoxidized linseed oil; Fly ash; Mechanical properties; Perlite; Thermal conductivity